Graduates’ perception of the value of ethics courses in university: A case study of UUM alumni - Mohamed, Mahmood N.; Marican, Sabitha (Sekolah Pembangunan Sosial, 2006)
Ethics is generally defined as the science of moral or moral discipline. The study of ethics can provide some general prescriptions that can be used to define problems and use its basic principles to solve problems pertaining to ethical and moral issues. In the Malaysian culture, ethics is defined as the learning and knowledge acquired for the sake of right living. It is a concept of what a person should know, be and do. Apart from the acquisition of knowledge, it is generally agreed that a wholesome university education should also address the issue of building the character of the individual. Specifically the study of ethics may provide a strong basis for the development and improvement of The study of ethics can be traced back to the days of ancient Greece, and through time, philosophers have argued the subject matter from various standpoints. Issues pertaining to values and moral are also very synonymous to ethics and they are frequently discussed in the context of each other (Kerner, 1966; White, 1992). Ethicsis derived from the Greek word ethos, meaning character and moral is from the Greek word moralis meaning customs or manners. Ethicsis a construct that is primarily used pertaining to the individual character of a person, whereas moral is the relationship between human beings. However, the construct of ethics and moral are often used interchangeably (White, 1992; Thiroux, 1995; Denise, Peterfreund & White, 1999).In philosophy, ethicsis a specific area ofstudy, which isthe study on morality and for the most part, concentrates on the human conduct and values. In fact, ethics has also been defined as the science of moral or moral discipline. It is concerned with goodness and badness of character or disposition, or with the distinction between right and wrong. Therefore, we always refer to ethics or moral in the context of the person (an ethical worker) or to a specific act (lying is an immoral act) (Thiroux, 1995). In specific terms, when we talk about ethics, we usually mean normative ethics. The other is known as metaethics. The earlier concept refers to theories that are based on valid moral principles; these are actual moralstatements(for example, abortion is wrong). The central feature of normative ethicsisthe moral principle (White, 1992, Mahoney, 1990). Principles are generally guidelines for the right conduct (for example, ethical conduct for theories are intentionally general so that they may apply to every situation we are likely to encounter (for example, do not unnecessary harm others). UUM believes that these basics must be taught at the tertiary level so that students can understand the underlying principles of good, moral and ethical behavior, asit can act as a foundation for their conduct. Metaethics, on the other hand is the theoretical study centered on the analysis and meaning of the language used in ethical discourse and the logic used to justify ethical reasoning. Their concern is conceptual analysis and inquiry into the correct method for answering moral questions (White, 1992; Percesepe, 1995; Denise, Peterfreund & White, 1999). This has been one application especially useful to social science students, who dwell in areas of reasoning and generalization (Cherrington, 1998). For the social scientist, the examination of moral behaviors entailsthe processes of definition, classification and generalization. We observe and compare mores, customs, traditions, morals and laws of different societies and formulate theories about the roles of morals in society; we study the relationships between moral and other variables such as criminality, deviance, equity and productivity, and therefore formulated that one’s character. This study is related to the experience of UUM in the teaching of ethics to undergraduate students. It focuses on the perception of UUM alumni on the ethics courses that they studied while in UUM and the level of usefulness of these subjects to their current profession and standing. Analysis was performed across several variables such as gender, ethnic groups, academic performance, present occupation and salary. The results show some association in student perception towards the usefulness of these ethics courses taught in the university according to gender, ethnic, geographical location and some achievement variables.